A Comprehensive Evaluation of OEE as a Production Monitoring Tool for a Diverse Manufacturing Environment - Kupila, Carlo (My University, 2024)
This thesis examines the effectiveness of Overall Equipment Efficiency (OEE) as a production monitoring tool in diverse manufacturing environments through four case studies. The research evaluates OEE's ability to meet stakeholder needs and provide meaningful insights into production processes. Each case study is conducted in a real-life setting with varied production equipment, highlighting the actual challenges posed by the lack of standardization in OEE implementation and data collection methods. The findings reveal significant variability in reported OEE numbers, difficulties in accurately determining production states, and the absence of benchmarking mechanisms. While OEE offers insights into potential production losses, the cases fall short of achieving the OEE world-class level that is often considered a production goal. The main reasons behind the challenges in production monitoring are the issues posed by the diverse environment and the lack of universal applicability of OEE as a standardized production eval-uation metric. The study underscores the importance of tailoring the definitions of the factors contributing to OEE and employing accurate data collection methods to enhance the utility of OEE. Additionally, the thesis suggests using complementary key performance indicators and downtime analysis to provide comprehensive in-sights into machine performance and production efficiency. While OEE has its place in monitoring overall equipment efficiency and the successful inclusion of TPM in a homogeneous production environment, the overall conclusion underscores the need for customized approaches to production monitoring. The KPI customization is essential to address the unique requirements of diverse manufacturing environments and to effectively meet varying production monitoring needs.
Keywords: OEE, production monitoring, overall equipment efficiency